LEXICAL MEANINGS OF WORDS IN GERMAN AND UZBEK LANGUAGES (AS THE EXAMPLE OF A WORD WATER) - Shohsanam Kodirova (International Scientific and Current Research Conferences, 2022)
This article discusses the lexical semantic relationships of lexemes and demonstrates their similarities and differences in different languages using the method of comparison. This situation is compared by comparing the lexical meanings of the word "water" in German and Uzbek, and the cases of disproportion between them are explained with the help of examples. This analysis explains the reasons for the differences in the meanings of words in languages. List the factors that affect the perception of the word.